Bercermin - Inspirasi dari Subroto Sm : Kompetensi Dosen Seni Rupa - Amir Hamzah (Ars: Jurnal Seni Rupa dan Desain, 2011)
Artistic biggest contribution in filling independence is upholding of art education which finally can round into the higher education fine arts. As high institute of education, Institut Seni Indonesia Yogyakarta which its age have stepped on 27 year, by increasing old age expected by earn really have mirror to more to developing of himself, upgrading and its role. Will be more be good if started with how this institution can esteem the himself. Can leave from problems of celebration of duty post of a lecture, momen esteem the part of himself, for avand garda of art education which have spilled sweat and its science. Now, with the time and situation that of is dissimilar Mister Subroto finally also propose its friends enter a period of pension. Become important to place the himself in an condition which finally one would consider or pay attention to it to be rewarded. Mister Subroto have the meaning is necessary for his colleague in ISI Yogyakarta, what will be at its place institute serve them. Mister Broto also deputize the other pensioner, what of course later have the history of about public road live as the officer and go together the its place institute work.Keywords: mirror, conpetence, appreciation,celebration, pension.